Composting of Municipal garbage by Using Trichoderma - A New Approach in Context of Bangladesh - Ilias, GNM; Rahman, MA; Molla, AH; Begum, MF; Alam, MF (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available.Key words: Trichoderma spore suspension; effective microorganisms EM; garbage-organic fertilizer; bio-digester; garbage cutter machine Bangladesh j. genet. biotechnol. 6 (1&2): 75-78, 2005 (June & December)